2008
DOI: 10.1387/ijdb.072315kd
|View full text |Cite
|
Sign up to set email alerts
|

A novel, neural potential of non-hematopoietic human umbilical cord blood stem cells

Abstract: From the time of discovery that among the cord blood mononuclear cell population there are cells capable of changing their fate towards the neural lineage and producing functional neurons and macroglial cells, our attempts have been focused on the understanding of the underlying mechanism of this transition. We have deciphered the first steps of neural stem/ progenitor gene induction in aggregating culture of cord blood mononuclear cells, their rapid phenotypic conversion under the influence of neuromorphogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 106 publications
1
20
0
Order By: Relevance
“…47 The HUCBNP cell population characterized in this study resembles in certain features the earlier reported unrestricted somatic stem cells isolated from cord blood. 46 The microarray gene expression analysis of HUCBNP indicates that the cells are negative for the hematopoietic markers CD34, CD49c, CD49d, CD62e, CD62p, CD106, CD117, CD133 (as also verified by immunophenotyping), CD235a , HLA-DRB4, HLA-DRB4 and HAS1, and positive for the mesenchymal markers CD13, CD29, CD44, CD49a/b (verified by Western), 6 CD49e, CD73, CD105 and vimentin.…”
Section: Figuresupporting
confidence: 77%
“…47 The HUCBNP cell population characterized in this study resembles in certain features the earlier reported unrestricted somatic stem cells isolated from cord blood. 46 The microarray gene expression analysis of HUCBNP indicates that the cells are negative for the hematopoietic markers CD34, CD49c, CD49d, CD62e, CD62p, CD106, CD117, CD133 (as also verified by immunophenotyping), CD235a , HLA-DRB4, HLA-DRB4 and HAS1, and positive for the mesenchymal markers CD13, CD29, CD44, CD49a/b (verified by Western), 6 CD49e, CD73, CD105 and vimentin.…”
Section: Figuresupporting
confidence: 77%
“…S2 C and D). Moreover, CD133 + cells did not spontaneously give rise to neuronal cells when maintained under neural culture conditions for a long period (21,22).…”
Section: Resultsmentioning
confidence: 95%
“…S2 C and D). Moreover, CD133 + cells did not spontaneously give rise to neuronal cells when maintained under neural culture conditions for a long period (21,22).Our initial attempts to convert Sox2-infected CB cells into neurons by using standard neural condition cultures were unsuccessful and infected CD133 + cells underwent apoptosis. Instead, we found that coculture with irradiated human foreskin fibroblasts (i.e., HFF-1 cells) in the presence of bFGF (23) (Fig.…”
mentioning
confidence: 99%
“…In vitro by RT-PCR, alizarin red and von Kossa-staining, ALP detection, immunohistochemistry and western blot 8,31,[110][111][112][113] In vitro by safranin-O staining, RT-PCR and immunohistochemistry 8,31 In vitro by immunohistochemistry, RT-PCR, calcium imaging and western blot [114][115][116][117] In vivo in parkinsonian rat model, ischemic rat model [118][119][120][121][122][123] In vitro by immunohistochemistry, RT-PCR, PAS-staining, urea and albumin production, western blot and LDL uptake 31,94,124,125 CD34/AC133-positive (hematopoietic progenitor) cells In vitro by RT-PCR 126 In vivo in NOD/SCID mouse model 95,96 Not defined cells from MNC In vitro by immunohistochemistry, whole-cell patch-clamp, western blot and RT-PCR [127][128][129][130][131] In vivo in spinal cord injury and intra-brain injection in rat and NOD/SCID mouse model 73,76,[80][81][82][83][84][86][87][88][89][90][91][92]<...>…”
Section: Mscmentioning
confidence: 99%